Climate Risk Mapping in the Philippines for Sub-National Targeting and Prioritization for Crop Diversification to Increase Resilience of the Agricultural Sector - Bragais, Milben; Mohanty, Samarendu; Baruah, Sampriti (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This study aimed to map “municipality-level” coverage of all high risk zones in the Philippines in high resolution using a compilation of official hazard and available socio-economic dataset to support climate change adaptation through agricultural diversification. The approach focused on assessing the risk of climate-related impacts (hazards) that may negatively affect agricultural communities. Thus, high-risk zones to climate change, variability and extremes was assessed and mapped in all municipalities in the Philippines using spatial modeling and statistical analysis of climate hazards and poverty incidence. The analyses focused on key climate risk that threatens the productivity of agricultural commodities in the Philippines at the municipal resolution where significant decision making and planning takes place, especially in the agricultural sector.